Illness and treatment beliefs and health outcomes in chronic pain: a meta-analysis. - Hagger, Martin S.; McKinley-Rodriguez, Lauren E.; Hamilton, Kyra (Psychology & Health, 2026)
Objective: Guided by the common-sense model of illness self-regulation, we examined zero-order and unique associations between illness and treatment beliefs and functioning and illness outcomes in a synthesis of research on chronic pain patients, and tested moderator and covariate effects on these associations. Methods and Measures: Studies reporting associations between illness and treatment beliefs and outcomes in chronic pain patients (k = 93, N = 18,262) were identified in a systematic database search. Data were analyzed using multi-level meta-analysis and meta-analytic structural equation modeling (MASEM). Results: We found averaged zero-order intercorrelations among the illness and treatment beliefs and chronic pain outcomes (physical and psychological impairment, disease status, social/role functioning). Moderator analyses indicated that relations between perceived consequences and social/role functioning were larger, and between emotional representations and illness status smaller, in patients diagnosed with a pain condition relative to those without a diagnosis. MASEM indicated unique effects of perceived control and consequences beliefs on physical impairment, causal beliefs on psychological impairment, identity beliefs on disease status, and treatment beliefs on social/role functioning. Conclusions: Findings identify belief-based correlates of pain-related outcomes and provide formative evidence to guide pain management intervention strategies. Future longitudinal and experimental studies should permit causal inferences in model effects and test coping strategies as a candidate mechanism.